2019
DOI: 10.1128/mbio.00614-19
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of a Natural Competence-Associated Pilin Suggest a Unique Pilus Tip-Associated DNA Receptor

Abstract: Natural competence is the term used to describe the uptake of “naked” extracellular DNA by bacteria; it plays a significant role in horizontal genetic exchange. It is associated with type IV pili, and specialized competence pili mediate DNA uptake. Here, we show that the crystal structure of a competence-associated protein from Thermus thermophilus, ComZ, consists of a type II secretion pseudopilin-like domain, with a large β-solenoid domain inserted into the β-sheet of the pilin-like fold. ComZ binds with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 75 publications
2
33
0
Order By: Relevance
“…9). However, recent studies have shown that the tip of the filament is important for DNA binding in Vibrio cholerae 49 , and it has been suggested that the Thermus filament cap may be comprised of the minor pilin PilA2 and ComZ, a DNA-binding protein 50 . In addition, functional experiments in Thermus have shown that pili are not absolutely required for natural transformation.…”
Section: Discussionmentioning
confidence: 99%
“…9). However, recent studies have shown that the tip of the filament is important for DNA binding in Vibrio cholerae 49 , and it has been suggested that the Thermus filament cap may be comprised of the minor pilin PilA2 and ComZ, a DNA-binding protein 50 . In addition, functional experiments in Thermus have shown that pili are not absolutely required for natural transformation.…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of antibiotic resistance, T4P are considered as a target for innovative antibacterial therapeutics [61]. T4aP of EHEC, among others, have been shown to be involved in biofilm formation, twitching motility and adherence [60]. The core minor pilins that likely form the tip of the pilus might play multiple roles, being at the same time responsible for the initiation of pilus formation, capping the pilus, and mediate specific biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Some non-core minor pilins have large structural insertions. The recently determined structure of the minor T4a pilin ComZ from T. thermophilus [60] shows an unusual structure with two domains, a pilin-like domain and a large additional domain inserted into its β-sheet. Hence, although not involved in pilus assembly, this minor pilin is likely located at the tip of the pilus, since the structural organization and the large size of this additional domain cannot allow upward incorporation of major pilins.…”
Section: Structure and Function Of Non-core Minor Pilinsmentioning
confidence: 99%
“…The uptake of exogenous DNA, known as natural competence, allows cells to adapt to environmental conditions through the exchange of situationally useful genes. Competence is known to depend on functional T4P in several bacteria [ 81 , 127 ], with DNA binding by T4P likely occurring at the pilus tip [ 128 , 129 ].…”
Section: Cyanobacterial Natural Competence Requires T4pmentioning
confidence: 99%